Hidden Transcripts of the Powerful: Researching the Arts of Domination. - Massoumi, Narzanin; Morgan, Marcus (Sociology, 2024)
This article develops a submerged aspect of James C Scott's work on 'hidden transcripts'. Whereas Scott focused predominantly on the hidden transcripts of the powerless, here we propose a research agenda based upon studying hidden transcripts of the powerful. First, we define our terms. Second, we map existing literature, observing that although plenty of research exists into the public transcripts of dominant and subordinate groups, and that Scott initiated a productive research agenda into the hidden transcripts of powerless groups, research into hidden transcripts of powerful actors is lacking. We identify an assumption within this literature that because existing social institutions are already structured in such a way as to reflect and advance the interests of dominant groups, there is no need for separate spaces to foster the consciousness, cohesivness, and mobilisation of the powerful. Third, we ask how social scientists might study the hidden transcripts of the powerful, and what methodological challenges and opportunities such a research programme might present, identifying in particular the promising avenue of studying what we have chosen to call 'transcripts hidden in plain sight'. Fourth, and finally, we question the epistemological status of these hidden transcripts, focusing on whether they can be used by social researchers as a reliable indicator of the 'true' consciousness of the social group that expresses them.